Do foreign investment, human development index, labor, and poverty influence economic growth in Indonesia? - Gahari, Radya Rayhan Muhammad; Hasmarini, Maulidyah Indira (Journal of Economics Research and Policy Studies, 2024)
Economic growth is one of the primary indicators of a country's success in improving the welfare of its people. In Indonesia, the dynamics of economic growth are highly complex and intriguing to study. This research aims to assess the impact of foreign investment, the human development index, labor, and poverty levels on economic growth in Indonesia. The method employed is a quantitative approach using data from 34 provinces in Indonesia between 2020 and 2022, obtained from the official BPS website. The analysis was conducted using panel data. The findings, using the FEM approach, indicate that individually, foreign investment, the human development index, and labor positively contribute to economic growth, while poverty does not have a significant impact. Overall, foreign investment, the human development index, labor, and poverty collectively influence economic growth in Indonesia. Therefore, the government should enhance economic growth by increasing foreign investment through stable policies, investing in education and healthcare, and ensuring a skilled workforce that meets market demand.